2019
DOI: 10.1051/0004-6361/201834724
|View full text |Cite
|
Sign up to set email alerts
|

Using evolutionary algorithms to model relativistic jets

Abstract: Context. High-resolution Very-Long-Baseline Interferometry (VLBI) observations of NGC 1052 show a two sided jet with several regions of enhanced emission and a clear emission gap between the two jets. This gap shrinks with increasing frequency and vanishes around ν ∼ 43 GHz. The observed structures are due to both the macroscopic fluid dynamics interacting with the surrounding ambient medium including an obscuring torus and the radiation microphysics. In order to model the observations of NGC 1052 via state-of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…The cold gas in the torus can be photoionized by UV photons from the inner accretion disk and the mixture of thermal and non-thermal material could be responsible for the strong depolarization of the inner regions via Faraday rotation-and one speaks of Faraday depolarization. In the case of NGC 1052, Fromm et al (2018Fromm et al ( , 2019 created synthetic radio maps of the jets using special-relativistic hydrodynamic simulations and suggested that an obscuring torus can explain some of the observed properties of these jets. In fact, the presence of a massive (∼10 7 M e ) and dense (> 10 7 cm −3 ) molecular torus has been recently demonstrated with ALMA observations (Kameno et al 2020).…”
Section: Depolarization In Radio Galaxiesmentioning
confidence: 99%
“…The cold gas in the torus can be photoionized by UV photons from the inner accretion disk and the mixture of thermal and non-thermal material could be responsible for the strong depolarization of the inner regions via Faraday rotation-and one speaks of Faraday depolarization. In the case of NGC 1052, Fromm et al (2018Fromm et al ( , 2019 created synthetic radio maps of the jets using special-relativistic hydrodynamic simulations and suggested that an obscuring torus can explain some of the observed properties of these jets. In fact, the presence of a massive (∼10 7 M e ) and dense (> 10 7 cm −3 ) molecular torus has been recently demonstrated with ALMA observations (Kameno et al 2020).…”
Section: Depolarization In Radio Galaxiesmentioning
confidence: 99%
“…To illustrate the jet imaging possibilities with Space VLBI, we consider the jet model by [29][30][31]. VLBI observations of radio galaxies reveal highly collimated jets surrounded by obscuring dusty tori.…”
Section: Physics Of Inner Jets In Agnmentioning
confidence: 99%
“…This is consistent with a globally averaged column density of (1−2) × 10 23 cm −2 estimated from X-ray observations (Baloković et al 2021). This results in an emission gap between both jet cores at frequencies below 43 GHz; see modelling by Fromm et al (2018Fromm et al ( , 2019. At centimetre(cm)-wavelengths the mean speeds of features in both jets have been derived as β ≤ 0.39 (Vermeulen et al 2003;Böck 2012;Lister et al 2019).…”
Section: Introductionmentioning
confidence: 96%